Faculty workload and employment benefits in public universities - Basarudin, Noor Ashikin; Yeon, Asmah Laili; Yaacob, Nurli; Yusof, Rohana @ Norliza (2016)
Malaysian Public Universities are undergoing the process of transformation which requires efforts from every components of the universities, especially the academic staffs, in order to achieve high rankings internationally and to fulfill their key performance indicator for the purpose of promotion and appraisal.These ambitions have increased the workload of academic staffs and extend their workloads from teaching to other myriad of responsibilities such as; research, consultation, administrative works and community services. In light of this, the benefits received by the academic staffs are disproportionate with their workloads.This research examines the relationship between transformation of higher education status, the workload of academic staff and the proportionality of benefit allocated to them. Data was collected through interview with the top level management from four different categories of universities such as Accelerated Program for Excellence, Research, Focused and Comprehensive University.Thematic content data analysis technique was employed in analyzing the data collected.The findings shows that the transformation of higher education status has intricate the workloads of academic staffs with less benefits.The workloads and job specifications of the academic staffs are different in accordance to the categories of the universities. Meanwhile, all public universities are bound to follow the standard scheme provided by the Public Service Department of Malaysia.This study suggests that the contract of service of academic staffs be revised to include clear terms on the improvement of scheme and benefits for academic staffs in public universities.